TEKNIK SENI LUKIS KLASIK BALI GAYA KAMASAN KARYA I NYOMAN MANDRA - Suyasa, I Nyoman; Gozali, Amir (Acintya, 2015)
One of the most popular Bali Klasik (classical Bali) painting arts is the painting of Wayang Kamasan.Â It is called that because it comes from Kamasan village, Klungkung. Formerly, the painting formÂ follows the form of wayang kulit. The figures are painted in thin form of two dimensions with theÂ stories taken from epos Ramayana and Baratayuda, stories from Malat Panji (stories of the 12 -14centuries), the theme of â€œPelelintanganâ€ that forecast about the effect of earthquake in our lives, andÂ also the theme of folk stories such as Men Brayut as a mother who has many children. Object of thisÂ article is the painting arts of Wayang Kamasan as the classical Balinese painting that takes root anddevelops in the local culture. The article stresses on the studies of visual art of Wayang KamasanÂ especially on the design and process of making. The previous library results are used to analyzeÂ technique and the creative process of Wayang Kamasan creating by I Nyoman Mandra. SomeÂ methods of approach are used directly towards the craftsmen and the existing musicians especially IÂ Nyoman Mandra. The article also uses literature studies with the theoretical approach to solve theÂ problems. The aesthetic theory of sanggit says that an art work represents a reproduction form withÂ treatment innovation and a sanggit work with revitalization concept. The work has an interest refersÂ to the conservation form of traditional art by giving the alternative works with reproductiontechnique of treatment innovation. Technically, it experiences the processing reduction through theÂ elements, contour lines, coloring technique, and the field content as well as changes of the storyÂ theme. The art of revitalization vitally and mainly refers to the traditional arts. The work uses strategyÂ of conservation concept by mutrani (nunggak semi). The result of research shows that Mandraâ€™s workÂ has followed the proportion and structure formulated in traditional aesthetics, but he also adds hisÂ own unique citra at the work. His work is characterized by a high delicacy, a lofty delicate value thatÂ is Bali traditional art, WayangKamasan.Keywords: painting arts of Klasik Bali, Kamasanstyle, technique.